The role of specific allocation fund on the local government budget timeliness - Provita Wijayanti; Dwi Ria Latifa (Jurnal Inovasi Ekonomi, 2020)
Local government budget (APBD) is the annual financial planning of the local government in Indonesia that requires consent from the Regional House of Representatives (DPRD) and is determined by regional regulation. One of the budgets is a fiscal balance which includes a revenue-sharing Fund (DBH), a general allocation fund (DAU), and a specific allocation fund (DAK). This study aims to analyze the role of funds allocation from the central government on the promptness of APBD establishment. The populations of this research were local governments in Central Java in periods 2014-2017. The data were obtained from the audit board (BPK) office and regional financial and asset management board (BPKAD) office in Central Java. This study is analyzed by logistic regression. The outcomes of this study indicated that DAK has a significant positive effect on the promptness of APBD establishment, whereas DAU and DBH have an insignificant negative impact.